Polymer Cancerostatics Targeted with an Antibody Fragment Bound via a Coiled Coil Motif: In Vivo Therapeutic Efficacy against Murine BCL1 Leukemia - Pechar, Michal; Pola, Robert; Janoušková, Olga; Sieglová, Irena; Král, Vlastimil; Fábry, Milan; Tomalová, Barbora; Kovář, Marek (Macromolecular bioscience, 2018)
A BCL1 leukemia-cell-targeted polymer-drug conjugate with a narrow molecular weight distribution consisting of an N-(2-hydroxypropyl)methacrylamide copolymer carrier and the anticancer drug pirarubicin is prepared by controlled radical copolymerization followed by metal-free click chemistry. A targeting recombinant single chain antibody fragment (scFv) derived from a B1 monoclonal antibody is attached noncovalently to the polymer carrier via a coiled coil interaction between two complementary peptides. Two pairs of coiled coil forming peptides (abbreviated KEK/EKE and KSK/ESE) are used as linkers between the polymer-pirarubicin conjugate and the targeting protein. The targeted polymer conjugate with the coiled coil linker KSK/ESE exhibits 4× better cell binding activity and 2× higher cytotoxicity in vitro compared with the other conjugate. Treatment of mice with established BCL1 leukemia using the scFv-targeted polymer conjugate leads to a markedly prolonged survival time of the experimental animals compared with the treatment using the free drug and the nontargeted polymer-pirarubicin conjugate.
Keywords: Immunoglobulin Fragments; drug targeting; leukemie; Humans; Cyclin D1; Drug Carriers; Molecular Targeted Therapy; Antibodies, Monoclonal; Click Chemistry; click chemie; Drug Delivery Systems; lidé; zvířata; imunoglobuliny - fragmenty; myši; peptidy; Mice; Peptides; polymery; Acrylamides; akrylamidy; Polymers; hydrophilic polymer; imunokonjugáty; lékové transportní systémy; cílená molekulární terapie; nosiče léků; cancer therapy; monoklonální protilátky; Immunoconjugates; coiled coil; cyklin D1; scFv; Leukemia; Animals; Disease Models, Animal; modely nemocí na zvířatech